The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/978-3-642-42039-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Currency Crises, Exchange Rate Regimes and Capital Account Liberalization: A Duration Analysis Approach

Abstract: This paper empirically analyzes the effect of exchange rate regimes and capital account liberalization policies on the occurrence of currency crises for 21 countries over the period of1970-1998. We examine changes of the likelihood of currency crises under de jure, and de facto exchange rate regimes. We also test whether the impact of the exchange rate regimes on currency stability would be different under free and restricted capital flows. Our findings show that the likelihood of currency crises changes signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…On the one hand, excessive money supply leads to currency crisis. On the other hand, less money supply leads to liquidity crunch in the onset of a crisis (Karimi & Voia, 2014). 7.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…On the one hand, excessive money supply leads to currency crisis. On the other hand, less money supply leads to liquidity crunch in the onset of a crisis (Karimi & Voia, 2014). 7.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Columns (5)-(8) in Table 4 show that seigniorage increases the odds of currency crises, confirming the fiscal theory of currency crises (Daniel 2001). In addition, capital account openness decreases the probability of currency crises (Column 8), as it offers more flexibility in the implementation of the monetary policy under fixed regimes (Esaka 2010a, 2010b, Karimi and Voia 2014. Finally, the fiscal balance (FB) does not matter in the prediction of currency crises: what matters is not whether governments generate fiscal deficits, but rather the way they finance them.…”
Section: Control Variablesmentioning
confidence: 97%
“…The major questions are how and when to liberalise, process of liberalisation and the pace of liberalisation the nations should follow. The major concerns for the economies till date are the negative impacts of openness of the economies, exposure of capital and money markets to the international markets and resulting in crises thereof (Karimi & Voia, 2011; Stiglitz, 2003). Emerging economies should restrict capital flows under weak market situation (Eichengreen et al, 1995) and implementation of Tobin tax is suggested on short-term to medium-term capital flows.…”
Section: Introductionmentioning
confidence: 99%